Student evaluation of teaching prior, during and after the COVID-19 pandemic - Pusker, Máté; Takács, Szabolcs; Takács, Rita (Frontiers in Education, 2025)
IntroductionThe primary aim of this study is to determine whether the quality of education declined at a Hungarian university during the COVID-19 lockdown. Contrary to studies with smaller sample sizes, we analyzed SET results from the university's IT faculty (both undergraduate and postgraduate programs) to provide empirical evidence for the academic discourse on the quality of education before, during, and after the COVID-19 pandemic. Although controversy surrounds SET questionnaires regarding their validity, reliability, and application, valuable information can be extracted from student feedback.MethodThis research retrospectively investigates the quality of education during the COVID-19 pandemic by analyzing student evaluation of teaching (SET) questionnaires at a Hungarian university collected from 2015 to 2022. This timeframe allows for a unique comparison between pre-COVID, COVID, and post-COVID educational periods, providing essential context for the pandemic's impact.ResultsOur analysis of SET questions yielded statistically significant results; however, the effect sizes were negligible (ϵ2 <0.01), indicating a lack of meaningful differences between the COVID and non-COVID periods.DiscussionResults suggests that despite the widespread disruption across all areas of life during the pandemic, the quality of education, with all its inherent challenges, did not substantially decrease in this Hungarian university.